Multi-omics study on the effect of moderate-intensity exercise on protein lactylation in mouse muscle tissue - Chang, Jiahui; Wu, Wanyu; Qian, Ping; Lu, Zhaoxu; He, Xuejia; Wang, Fang; Zhang, Ting (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThis study explores the effects of moderate-intensity exercise on protein lactylation in mouse muscle tissue metabolism.MethodsHealthy adult mice running for 6 weeks as an exercise model and sedentary mice as the control were used to perform transcriptomic, proteomic, lactylation-proteomic, and metabolomic analyses. Correlation analysis between transcriptome and proteome and between proteome and metabolome was also conducted.ResultsIn this study, 159 lactylation sites of 78 proteins were identified as being differentially regulated by moderate-intensity exercise. Enrichment analysis showed that the lactylation of proteins Atp5mg, and Atp5po exhibited ATP hydrolysis activity. Mtatp8 and Atp5po were involved in biological processes such as mitochondrial transmembrane transport, and Mtatp8, Atp5mg, and Atp5po participate in oxidative phosphorylation and thermogenesis pathways. The lactylation levels of Mtatp8, Atp5mg, and Atp5po proteins in the exercise group were significantly decreased, while their protein levels were significantly increased. The combined analysis of proteomics and metabolomics showed that the oxocarboxylic acid metabolism and sphingolipid signaling pathways had significant changes under the influence of moderate-intensity exercise.DiscussionOur results indicate that moderate-intensity exercise has an effect on the lactylation level of mice, possibly by reducing the lactylation levels of Mtatp8, Atp5mg, and Atp5po and increasing the expression of their protein levels, thereby regulating the oxidative phosphorylation pathway and participating in energy metabolism. Further exploration is needed into the 2-oxocarboxylic acid metabolism pathway and the sphingolipid signaling pathway.